Pengembangan Media Pop-Up Book Digital Bermuatan Lokal Kalimantan Timur pada Materi IPAS Kelas V - Siti Mutmainah Iis Yuliani; Sukriadi; Taufik Hidayat; Iksam (JANACITTA, 2025)
Abstract The background of this research is the lack of modern and interactive learning resources that integrate technology into the learning process. As a solution, a digital Pop-Up Book about natural wealth was created for fifth-grade elementary school students in the IPAS subject. This media is based on the local wisdom of East Kalimantan. The main objective of this development is to enhance students' appreciation of local culture and make the material easier to understand. Analysis, design, development, implementation, and evaluation are the five steps in the research and development (R&D) method using the ADDIE model. The subjects of the research are fifth-grade students of SD Negeri 008 Samarinda Ilir. Data collection was conducted through observation, interviews, and questionnaires. The trial participants, including teachers, students, media experts, language experts, and content experts, were involved in the data collection process. The validation results indicate that this learning media falls into the "Very Valid" category, with scores of 88.33% from Subject Matter Expert 1, 93.33% from Subject Matter Expert 2, 86.15% from Media Expert 1, 92.30% from Media Expert 2, and 96% from Language Expert. Additionally, the practicality test results were excellent, with a 94% response rate from teachers, 91.27% from the large group trial, and 89.25% from the small group trial. The results show that the digital Pop-Up Book, based on the local wisdom of East Kalimantan, is valid and suitable for use as a learning tool for fifth-grade elementary school IPAS. Abstrak  Latar belakang penelitian ini adalah kurangnya sumber belajar modern dan interaktif yang mengintegrasikan teknologi ke dalam proses pembelajaran. Sebagai solusi, sebuah Pop-Up Book digital tentang kekayaan alam dibuat untuk peserta didik kelas V SD dalam mata pelajaran IPAS. Media ini didasarkan pada kearifan lokal Kalimantan Timur. Tujuan utama pengembangan ini adalah untuk meningkatkan apresiasi peserta didik terhadap budaya lokal dan membuat materi lebih mudah dipahami. Analisis, desain, pengembangan, implementasi, dan evaluasi adalah lima langkah dalam metode penelitian dan pengembangan (R&D) dengan model ADDIE. Subjek penelitian adalah peserta didik kelas V SD Negeri 008 Samarinda Ilir. Pengumpulan data dilakukan melalui observasi, wawancara, dan angket. Para peserta uji coba, termasuk guru, peserta didik, ahli media, ahli bahasa, dan ahli materi, terlibat dalam proses pengumpulan data. Hasil validasi menunjukkan bahwa media pembelajaran ini termasuk dalam kategori "Sangat Valid,” dengan skor ahli materi 1 sebesar 88,33%, ahli materi 2 sebesar 93,33%, ahli media 1 sebesar 86,15%, ahli media 2 sebesar 92,30%, dan ahli bahasa sebesar 96%. Selain itu, uji coba kepraktisan menunjukkan hasil yang sangat baik, dengan respons guru sebesar 94%, uji coba kelompok besar sebesar 91,27%, dan uji coba kelompok kecil sebesar 89,25%. Hasilnya menunjukkan bahwa Pop-Up Book digital, yang didasarkan pada kearifan lokal Kalimantan Timur, valid dan cocok untuk digunakan sebagai alat pembelajaran untuk IPAS kelas V SD.